Financial Performance Analysis to Reformulate Business Strategy (Case Study: Bank Syariah Mandiri KCP XYZ) - Rachmadiah, Euis; Aliludin, Arson (The Indonesian Journal of Business Administration, 2013)
The purpose of this research is to analyzing Financial Performance of KCP XYZ of PT Bank Syariah Mandiri in order to reformulate business strategy and its implementation plan. The strategy formulation is conducted with evaluating its current performance as a first stage element. Financial Performance analysis by 4 financial ratios; ROA, BOPO, NCOM, FDR and 4 growth ratios; Growth of Assets, Growth of Depositor Funds, Growth of Financing and Growth of Net Earnings, is chosen to evaluate the position of KCP XYZ comparing to other nine KCP under supervision of Regional R. This research is supported by the primary data (financial data) and secondary data (literature review).Based on financial performance and SWOT analysis results, the KCP XYZ strategy generated is concentration growth strategy. The alternative strategies to accomplish the growth strategy are generated through Ansoff matrix that include: market penetration, product development, market expansion to new markets, and product diversification. Through FGD, the decision of selected strategies and the implementation priority are: market penetration, product development strategy and market expansion.The implementation of the selected strategies are through developing integrated programs and action plan at each functional departments Ã‚Â Keyword: Financial ratios, Growth Ratios, SWOT, Ansoff Matrix